Mapping the landscape characters along a rural route for tourism - Abdul Wahab, Nur Amirah; Zakariya, Khalilah; Ibrahim, Putri Haryati; Ibrahim, Illyani (Malaysia Institute of Planners, 2018)
The scenic landscape characters along driving routes have been acknowledged by numerous studies to be important in planning for rural tourism. Landscape characters shape the setting and ambience of a place. This study focuses on mapping the landscape characters along a rural route as a way to identify potential characteristics to be conserved and enhanced for tourism. The case study area covers the Kuala Selangor to Sabak Bernam route, which is part of a federal route that runs along the west coast of Peninsular Malaysia. Using landscape character mapping, observation and landscape character assessment (LCA), mapping was conducted to identify and analyse the landscape characters along the route based on the physical, cultural and environmental attributes. It is found that each segment along the route has its own attributes and the physical images based on their activities and environment. This study found that the rural route has a unique and distinctive rural landscape identity that needs to be integrated with the planning of infrastructure and road system, in order for it to increase tourism activities.